Investigation of Allergic Sensitizations in Children With Allergic Rhinitis and/or Asthma - Lingman Dai; Jinling Liu; Qi Zhao; Qi Zhao; Mengyao Li; Yunlian Zhou; Zhimin Chen; Yuanyuan Zhang (Frontiers in Pediatrics, 2022)
ObjectiveAllergic rhinitis (AR) and asthma are becoming one of the most prevalent diseases in children. Identifying sensitization to aeroallergens is seemed to be valuable for diagnosing allergic disease and guiding its treatment. This study aimed to analyze the profiles of sensitization to aeroallergen in children with AR and/or asthma by skin prick test (SPT) and explore the differences of sensitization between different kinds of allergic diseases, different sexes, and different ages.MethodsA total of 230 children with AR and/or asthma who were hospitalized in our hospital from June 2017 to September 2019 were eligible in this retrospective study. All patients completed standardized questionnaires and SPT. Based on the sex, age, or classification of allergic disease, the sensitizations to 13 aeroallergens were compared.ResultsOf the 230 patients, 67.4% of enrolled were positive for SPT; the top 5 allergens were Dermatophagoides pteronyssinus (Der.p) (59.3%), Dermatophagoides farina (Der.f ) (58.7%), Blomia tropicalis (Blot.) (40.3%), dog hair (36.1%), and Blattella germanica (20.4%). More than 90% of patients were sensitized to two or more allergens. As to the effect of age on aeroallergens, we found that the sensitizations of Blot., dog fur, and multiple sensitizations (≥5 allergens) were more common in adolescence (P < 0.01, P < 0.05). Regarding sex, we found that the positive rate of SPT and the percentages of double-allergen sensitizations in boys were much higher than girls (P < 0.01, P < 0.01), and the positive rate to Der.p, Der.f , and ragweed were also significantly higher in boys (P < 0.01, P < 0.05, and P < 0.05, respectively). Furthermore, we found that asthma–rhinitis multimorbidity increased the incidences of sensitizations; patients with AR and asthma had significantly higher positive rates to Der.p and Der.f when compared with the AR or asthma group (P < 0.05, P < 0.05).ConclusionAllergic sensitizations were common in children with AR and/or asthma; sex, age, and asthma–rhinitis multimorbidity might affect the prevalence of sensitizations to aeroallergens.